2022
DOI: 10.1021/acs.analchem.2c02323
|View full text |Cite
|
Sign up to set email alerts
|

Attomole-Level Multiplexed Detection of Neurochemicals in Picoliter Droplets by On-Chip Nanoelectrospray Ionization Coupled to Mass Spectrometry

Abstract: While droplet microfluidics is becoming an effective tool for biomedical research, sensitive detection of droplet content is still challenging, especially for multiplexed analytes compartmentalized within ultrasmall droplets down to picoliter volumes. To enable such measurements, we demonstrate a silicon-based integrated microfluidic platform for multiplexed analysis of neurochemicals in picoliter droplets via nanoelectrospray ionization (nESI)-mass spectrometry (MS). An integrated silicon microfluidic chip co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…However, previously demonstrated on-chip integration of specially designed nanoelectrospray nozzles using our scaled silicon ND platform 29,30 may enable efficient MS hyphenation of pL-segmented dialysate flows with LOD of just a few attomoles. 31 The proposed and demonstrated scaling strategy (Figure 1b−d) can potentially be extended even further in miniaturizing the sampling area, while keeping a high recovery rate and temporal resolution. With mature silicon microfabrication technology, it is relatively straightforward to reduce the channel cross-section, and hence control the pressure-driven flow rates below 1 nL/min (Figure 1d).…”
Section: Discussionmentioning
confidence: 99%
“…However, previously demonstrated on-chip integration of specially designed nanoelectrospray nozzles using our scaled silicon ND platform 29,30 may enable efficient MS hyphenation of pL-segmented dialysate flows with LOD of just a few attomoles. 31 The proposed and demonstrated scaling strategy (Figure 1b−d) can potentially be extended even further in miniaturizing the sampling area, while keeping a high recovery rate and temporal resolution. With mature silicon microfabrication technology, it is relatively straightforward to reduce the channel cross-section, and hence control the pressure-driven flow rates below 1 nL/min (Figure 1d).…”
Section: Discussionmentioning
confidence: 99%
“…Integration with previously demonstrated hyphenation of segmented dialysate flows to sensitive MS methods using nano-ESI 29 or MALDI-MS 30 will enable quantification of small molecules at the level of just a few attomoles 31 . The proposed and demonstrated scaling strategy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further integration of on-chip droplet segmentation and a delay line for droplet storage enables sampling and manipulation of analytes at volumes of just a few pL. Integration with previously demonstrated hyphenation of segmented dialysate flows to sensitive MS methods using nano-ESI 29 or MALDI-MS 30 will enable quantification of small molecules at the level of just a few attomoles 31 . The proposed and demonstrated scaling strategy (Fig.1B,C,D) can potentially be extended even further in miniaturizing the sampling area, while keeping high recovery rate and temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As fabricated, the microfluidic channels are hydrophilic, hence oil is the segmented phase, while the aqueous phase is continuous. Previous MS measurements 28 of the potential carry-over of analytes between consecutive aqueous plugs have shown that carry-over of analytes in the oil-segmented aqueous flow between aqueous plugs of similar volume and frequency is suppressed by at least 3 orders of magnitude.…”
Section: Analyte Segmentationmentioning
confidence: 99%